Aktualisasi Program 7 Kebiasaan Anak Indonesia Hebat Era Digitalisasi Di SMAS NU Toboali - Fauzi; Siti Patimah; Nur Hidayah; M. Indra Saputra (IQRO: Journal of Islamic Education, 2024)
This study aims to analyze the implementation and relevance of the "7 Habits of Great Indonesian Children" program at SMAS NU Toboali in creating a high-quality learning process by instilling the steps of habitual good practices in students' daily lives. Through these good practices, the school can fulfill its function of producing a generation of students who are more competent and prepared to face the challenges of the digitalization era while also addressing the issue of moral degradation in the current context. The "7 Habits of Great Indonesian Children" program focuses on instilling excellent character values and cultivating students' habitual orderly lifestyles in their everyday lives with the guidance, direction, and supervision of parents and teachers at school. These good practices are essential for students to face the challenges of the times while maintaining their identity as a generation that is physically and mentally healthy, possesses integrity, and is adaptive and innovative.